2013
DOI: 10.1920/wp.ifs.2013.1313
|View full text |Cite
|
Sign up to set email alerts
|

Anti-smoking policies and smoker well-being: evidence from Britain.

Abstract: Anti-smoking policies can in theory make smokers better o, by helping smokers with time-inconsistent preferences commit to giving up or reducing the amount they smoke. We use almost 20 years of British individual-level panel data to explore the impact on self-reported psychological well-being of two policy interventions: large real-terms increases in tobacco excise taxes and bans on smoking in public places.We use a dierence-in-dierences approach to compare the eects on well-being for smokers and nonsmokers. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…2010). A recent literature also argues that there could be positive effects of a smoking ban on smokers when the ban acts as a self-control device and individuals are time inconsistent (Odermatt and Stutzer, 2015;Leicester and Levell, 2016). Our results show that the ban had a positive effect on the well-being of the population of non-smokers, and that these effects are felt by many different subgroups of the population.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…2010). A recent literature also argues that there could be positive effects of a smoking ban on smokers when the ban acts as a self-control device and individuals are time inconsistent (Odermatt and Stutzer, 2015;Leicester and Levell, 2016). Our results show that the ban had a positive effect on the well-being of the population of non-smokers, and that these effects are felt by many different subgroups of the population.…”
Section: Introductionsupporting
confidence: 61%
“…Support for this hypothesis can be found in Gruber and Mullainathan (2005), who show that higher taxes improve self-reported well-being of individuals with a higher propensity to smoke compared with those with a lower propensity to smoke. By contrast, Leicester and Levell (2016) show no significant association between smoking bans and individual well-being in the UK. Odermatt and Stutzer (2015) find that smoking bans in Europe are welfare enhancing only for individuals who would like to quit smoking.…”
Section: Welfare Effectsmentioning
confidence: 62%
“…Cheng et al, 2015) and the use of anti-smoking policies as self-control devices (e.g. Leicester and Levell, 2016). Overall, further research and larger datasets might be needed to more precisely establish the causal pathways leading to the observed increase in well-being following public smoking bans.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Hinks and Katsaros () employed UK data and found that smokers who reduce their intake of cigarettes after the ban report significantly lower levels of life satisfaction if compared to individuals who did not reduce their amount of tobacco intake (and smoked the same pre‐ban amount of cigarettes). Leicester and Levell () also exploited UK data and found that while tobacco excise taxes increase smokers’ well‐being, the impact of smoking bans appears to be weaker. Overall, these papers tend to overlook potential intra‐household well‐being externalities and appear to present conflicting results .…”
Section: Introductionmentioning
confidence: 99%
“…This is the case even when many of these smokers did not report to be in favour of the implementation of the smoking ban in the first place. Using twenty years of the British Household Panel Survey, Leicester and Levell (2016) show that increases in cigarette prices raise the happiness of likely smokers. However, the authors find no evidence that the introduction of a smoking ban across the U.K.…”
mentioning
confidence: 99%